The effect of big five personality traits on job satisfaction among support staff in Tech Art Sdn Bhd / Dinie Azfar Zabir - Zabir, Dinie Azfar (Faculty of Business and Management, 2013)
Nowadays, the big five personality traits is essential towards job's satisfaction. According to Udoudoh (2012), big five personality traits is a key personality factors, which to find the careers of one's dream that identified as job satisfaction. Based on past researches, big five factor model adequate to describe of personality goes beyond the levels of satisfaction adapted from Judge, (2002) as cited by Paul (2009). In the organization, job satisfaction is necessary to promote functional employees behaviors and workforce that is motivated and committed to elevated good presentation because job satisfaction is a vital indicator of how employees feel sense concerning their jobs and a predictor of work behaviors (Diksha & Shruti, 2012). Furthermore, job satisfaction additionally can partly arbitrate the connection of personality variables and deviant work behaviors (Diksha & Shruti, 2012). Personality traits can be an ilnportant factor and make a difference in job satisfaction because most of researchers found that there was a relationship between five personality traits studied and job satisfaction (Zeki M., 2011). Therefore, this study was carried out to identify the relationship between Big Five Personality Traits and job satisfaction among support staff in Tech Art Sdn Bhd.